The Use of Two New Formulations of Ocimum Canum Sims and Cymbopogon Schoenanthus L. In The Control of Amitermes Evuncifer Silvestri (Termitidae: Termitinae), in Togo - Norbert, Gbenyedji Koami Bezo Jean; Seth, Nyamador Wolali; Dodji, Kasseney Boris; Roger, Nebie Charles Honorat; Guillaume, Ketoh Koffivi; Essè, Anani Koto Klo; Isabelle, Glitho Adolé (International Journal of Natural Sciences Research, 2014)
Today, the main concern of farmers and scientists is finding an alternative to the use of chemical pesticides in pest management, environmental pollution prevention and poisoning of the population. For this purpose, more and more studies are being carried out on biopesticides from plants used in local pharmacopoeia for the management of insect pests of crops and food stocks. In this study, the effect of a mixture of essential oil of Ocimum canum Sims with starch and that of Cymbopogon schoenanthus with starch were separately evaluated against Amitermes evuncifer Silvestri, one of the main pestiferous termites in Togo. These formulations were prepared from each plant at six different concentrations with and without sawdust. They were effective and caused significant mortality of Amitermes evuncifer. The formulation of essential oil without sawdust was more effective than that with sawdust. For the formulation without sawdust, 75 and 38% mortality respectively were recorded with C. schoenantus and O. canum at a dose of 0.5 mg/cm2, while 100% mortality was recorded at 2 mg/cm2 for both plants in both formulations. However, between the two plants, the formulations made from S. schoenantus were more effective on A. evuncifer than those made from O. canum. These new formulations made from the essential oils and starch could be used as biopesticide to control pestiferous insects in the field.